Post-Crisis Management of High-End Domestic Tourism: Evidence from Thailand - Kenaphoom, Sanya; Sriwapee, Kanokwan; Ruangchai, Netnapa; Insumran, Yuwadee; Pawala, Thanyachanok; Jumroenpat, Paripon; Kaewlamai, Somboon; Nanposri, Natamon (International Journal of Multidisciplinary in Management and Tourism, 2025)
Thailand, one of the nations most dependent on tourism globally, had a severe economic shock during the COVID-19 pandemic as a result of its reliance on foreign tourists, which decreased by more than 83% in 2020. This crisis exposed deep flaws in the country's tourism sector and prompted a strategic shift toward supporting the local tourism market, particularly among affluent Thai visitors. The study aims to explore how Thailand changed its tourism strategy in response to the epidemic by concentrating on high-end domestic tourists. It examines shifts in consumer behavior, business advancements, and governmental laws to create a more resilient and regional tourism strategy. The research employs a qualitative case study methodology and uses secondary data sources such as government papers, publications from the tourism industry, expert analyses, and case studies from popular tourist locations like Phuket, Chiang Mai, Hua Hin, and Khao Yai. Comprehensive insights into tourism adaptation between 2020 and 2024 are provided via triangulated data collection. The findings show that wealthy Thai tourists diverted their funds to upscale domestic experiences that prioritize exclusivity, privacy, and well-being. In response, companies used digital marketing techniques, local collaborations, and service personalization. Subsidies and public-private infrastructure projects provided by the government were crucial. Hybrid tourism-real estate models have become more popular in places like Hua Hin and Khao Yai, while places like Phuket and Chiang Mai have effectively remade themselves for the local elite market. In conclusion, Thailand's transition to upscale domestic travel provided both a long-term resilience foundation and a cushion against the crisis. The strategic significance of market diversification, sustainable tourism growth, and inclusive policy design is emphasized in the paper. For other economies that rely on tourism and are trying to prepare their sectors for the future, these findings have important implications.